Efektivitas Diaphragm Breathing Exercise Terhadap Tingkat Kecemasan Ibu Hamil Trimester III di Praktik Mandiri Bidan Kota Padang - Ika Yulia Darma; Silvi Zaimy; Meldafia Idaman; Silfina Indriani (Universitas Batanghari Jambi, 2023)
The anxiety rate in pregnant women in Indonesia is quite high, namely 28.7% of which this anxiety is experienced by pregnant women in the third trimester before the delivery process. This has an impact on the physical, psychological and process conditions that will be undertaken by the mother, but it also affects the postpartum period. Diaphragm breathing exercise is one of the complementary therapies to overcome the anxiety experienced by pregnant women who have little risk. To determine the effectiveness of diaphragm breathing exercise on the anxiety level of pregnant women in the third trimester. Research Methods: This type of quantitative research uses a quasi-experimental method with one group pretest and posttest design. A total of 16 pregnant women TM III in Padang City Midwives Independent Practice were taken using purposive sampling technique. The measuring instrument used is the PRAQ-R2 (Pregnancy Related Anxiety Questionnaire- Revised) instrument. The effectiveness of the diaphragm breathing exercise on the anxiety of pregnant women with TM III was tested using Paired t-test with p-value < 0.05. Results: The results showed that the average level of maternal anxiety before the intervention was 29.68 and after giving diaphragm breathing exercise the anxiety level was 19.12 with an average difference of 10.56. The results of statistical tests showed that there was a significant effect between the anxiety level of pregnant women with TM III before and after being given diaphragm breathing exercise with a p value of 0.000 (p value <0.05). Conclusion: diaphragm breathing exercise is effective in reducing anxiety levels of pregnant women with TM III in the Independent Practice of Midwives in Padang City.